Enhanced Performance of Mg0.1Zn0.9O UV Photodetectors Using Photoelectrochemical Treatment and Silica Nanospheres. (5th March 2014) - Lee, Hsin-Ying; Lin, Yu-Chang; Lee, Meng-Ju; Uen, Wu-Yih; Sreenivas, Kondepudy
Abstract : The Mg0.1 Zn0.9 O films were grown using atomic layer deposition (ALD) system and applied to metal-semiconductor-metal ultraviolet photodetectors (MSM-UPDs) as an active layer. To suppress the dangling bonds on the Mg0.1 Zn0.9 O surface, the photoelectrochemical (PEC) treatment was used to passivate the Mg0.1 Zn0.9 O surface, which could reduce the dark current of the MSM-UPDs about one order. Beside, to increase more incident light into the Mg0.1 Zn0.9 O active layer of the MSM-UPDs, the 500-nm-diameter silica nanospheres were spin-coated on the Mg0.1 Zn0.9 O active layer to improve the antireflection capability at the wavelength of 340 nm. The reflectivity of the Mg0.1 Zn0.9 O films with silica nanospheres antireflection layer decreased about 7.0% in comparison with the Mg0.1 Zn0.9 O films without silica nanospheres. The photocurrent and UV-visible ratio of the passivated Mg0.1 Zn0.9 O MSM-UPDs with antireflection layer were enhanced to 5.85 μ A and 1.44 × 10 4, respectively, at the bias voltage of 5 V. Moreover, the noise equivalent power and the specific detectivity of the passivated Mg0.1 Zn0.9 O MSM-UPDs with antireflection layer were decreased to 2.60 × 10 - 13 W and increased to 1.21 × 10 12 cmHz 1/2 W −1, respectively, at the bias voltage of 5 V. According to the above mentions, the PEC treatment and silica nanospheres antireflection layer could effectively enhance the performance of Mg0.1 Zn0.9 O MSM-UPDs.